ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INDONESIA KELAS X DI SMAS SANTUN UNTAN - Selly, Natalia; Jupitasari, Mellisa; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2025)
This study aims to analyze (1) the implementation of the independent curriculum in the Indonesian language subject in class X SMAS Santun Untan, (2) evaluation of the independent curriculum in the Indonesian language subject in class X SMAS Santun Untan, (3) obstacles to the implementation of the independent curriculum in the Indonesian language subject in class X SMAS Santun Untan. The approach used in this study is a qualitative approach with a descriptive research method. Data collection techniques use observation, interview, and documentation techniques using data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions (data verification). The analysis in this study used eight informants, namely one core informant and 7 supporting informants. The results of the study indicate that the implementation of the independent curriculum in Indonesian language learning for class X has not been optimally implemented. The implementation of the independent curriculum is still collaborated with the 2013 curriculum, namely in the use of LKS as a learning tool. In addition, obstacles in implementing the independent curriculum are that many teachers are not tech-savvy or do not master technology, the lack of facilities and infrastructure at SMAS Santun Untan, and the limited ability of teachers to adapt to the independent curriculum are also quite serious obstacles experienced at SMAS Santun Untan. Evaluation of the implementation of the independent curriculum in Indonesian language learning at SMAS Santun Untan is divided into 2, namely written and oral assessments for students.